The Role of Women Merchants in Increasing Family's Income (A Case Study on Indigenous Papuan Women Merchants) - Dedi, Selmi; Toyib, Jein Sriana; Waimbo, Dani Erlis (Jurnal Aplikasi Manajemen, 2016)
This study was aimed atdeterminingthe contribution of Papuan women merch nts to the family's income development and pursue the role of government and financial institutions in supporting the business activities of Papuan women merchants.It was done in the Central market of Sorong, Sorong regency, Central market of Bintuni, Bintuni regency, Central market of Kajase, South Sorong regency, and Central market of Raja Ampat, Raja Ampat regency, focusing on Papuan women merchants. This study used 100 respondents. Data collection employed interviews and direct observation on socio-economic activities. Data analysis applied qualitative method. Results showed that mean monthly net income of Papuan women merchants in the traditional markets was high enough and mostly used for the household's income development with 60.47% contribution to total family's income.